The Distributed Morphology of Object Clitics in Modern French - Goldbach Maria (Zeitschrift für Sprachwissenschaft, 2007)
In modern French, as in all Romance languages, the combination of two object clitics is subject to rigid ordering and co-occurrence constraints. The present paper shows that constraints of both kinds can be ascribed to systematically operating impoverishment processes in the sense of Distributed Morphology (Bonet 1995; Halle & Marantz 1993) without recourse to templates (cf. Miller & Sag 1997; Perlmutter 1971, etc.). The system that will be presented below is consistent, complete and non-redundant. Thus, it fulfils the essential metatheoretical qualifications of a formal system. The assumption of this paper is that the object clitics are postsyntactically inserted dissociated morphemes that are, prior to further operations kicking in, preverbally linearized. The postposition present in the positive imperative is brought about by another, subsequent, postsyntactic operation, i. e. by local dislocation. Or, put another way, there is an operational level in which the object clitics are arranged before the verb. Only on a downstream operational level do the object clitics move behind the verb.